Effect of microthread design on the preservation of marginal bone around immediately placed implants: a 5-years prospective cohort study - Hoori Aslroosta; Solmaz Akbari; Nima Naddafpour; Seyed Taha Adnaninia; Afshin Khorsand; Niusha Namadmalian Esfahani (BMC, 2021)
Abstract Background This study aimed to evaluate the effect of the microthread design at the implant neck on the preservation of marginal bone around immediately-placed implants in a 5-year follow up. Methods Thirty patients received 41 immediately placed implants which were randomly assigned to treatment groups with microthreaded implants (test group, n = 22) or threaded implants (control group, n = 19). Clinical and radiographic analyses were carried out after 1 and5 years. Plaque index, bleeding on probing, suppuration, probing depth and marginal bone loss were subject to evaluations. The results were analyzed with the T-test, Fisher's exact test and Mann-Whitney U test. Results No implants failed; thirty-five implants (in 27 patients); 21 microthreaded and 14 threaded implants; completed the 5 year follow up. The mean values of the marginal bone loss in microthreaded and threaded groups were 1.12 ± 0.95 mm and 0.87 ± 0.78 mm, respectively during an observation period of 70.9 ± 10.4 months; the differences in marginal bone loss and other pre-implant parameters were not significant between groups (P > 0.05). Conclusion Both implant designs showed acceptable results in terms of the clinical parameters and marginal bone level. Within the limitation of this study, the results did not demonstrate any superiority of the microthread design compared to threaded one in marginal bone preservation around immediately placed implants over 5 years of loading.